Unprecedented N2O production by nitrate-ammonifying Geobacteraceae with distinctive N2O isotopocule signatures - Zhenxing Xu; Shohei Hattori; Yoko Masuda; Sakae Toyoda; Keisuke Koba; Pei Yu; Naohiro Yoshida; Zong-Jun Du; Keishi Senoo (mBio)
ABSTRACT Dissimilatory nitrate reduction to ammonium (DNRA), driven by nitrate-ammonifying bacteria, is an increasingly appreciated nitrogen-cycling pathway in terrestrial ecosystems. This process reportedly generates nitrous oxide (N2O), a strong greenhouse gas with ozone-depleting effects. However, it remains poorly understood how N2O is produced by environmental nitrate-ammonifiers and how to identify DNRA-derived N2O. In this study, we characterize two novel enzymatic pathways responsible for N2O production in Geobacteraceae strains, which are predominant nitrate-ammonifying bacteria in paddy soils. The first pathway involves a membrane-bound nitrate reductase (Nar) and a hybrid cluster protein complex (Hcp–Hcr) that catalyzes the conversion of NO2− to NO and subsequently to N2O. The second pathway is observed in Nar-deficient bacteria, where the nitrite reductase (NrfA) generates NO, which is then reduced to N2O by Hcp–Hcr. These enzyme combinations are prevalent across the domain Bacteria. Moreover, we observe distinctive isotopocule signatures of DNRA-derived N2O from other established N2O production pathways, especially through the highest 15N-site preference (SP) values (43.0‰–49.9‰) reported so far, indicating a robust means for N2O source partitioning. Our findings demonstrate two novel N2O production pathways in DNRA that can be isotopically distinguished from other pathways.IMPORTANCEStimulation of DNRA is a promising strategy to improve fertilizer efficiency and reduce N2O emission in agriculture soils. This process converts water-leachable NO3− and NO2− into soil-adsorbable NH4+, thereby alleviating nitrogen loss and N2O emission resulting from denitrification. However, several studies have noted that DNRA can also be a source of N2O, contributing to global warming. This contribution is often masked by other N2O generation processes, leading to a limited understanding of DNRA as an N2O source. Our study reveals two widespread yet overlooked N2O production pathways in Geobacteraceae, the predominant DNRA bacteria in paddy soils, along with their distinctive isotopocule signatures. These findings offer novel insights into the role of the DNRA bacteria in N2O production and underscore the significance of N2O isotopocule signatures in microbial N2O source tracking.